Relating to the text : interdisciplinary and form-critical insights on the Bible - Sandoval, Timothy J.; Mandolfo, Carleen; Buss, Martin J. (Journal for the study of the Old Testament. Supplement series ;, 2003)
This collection contains studies reflecting the contribution of Martin Buss to biblical scholarship, focusing on the forms and genres of biblical literature and on interdisciplinary approaches to biblical interpretation. Contributors to the volume include J.H. Hayes, J. Kuan, A. Siedlecki, B. Green, M. Miller, R. Bailey, S. Melcher, B. Long, N. Walls, C. Newsom, D. Blumenthal, T. Linafelt, T. Beal, E. Ben Zvi, N. Stipe, N. Habel, F. Gorman, Y. Gitay, J. Lapsley, M. Sweeney, E. Gerstenberger, V. Robbins, D. Jobling, R. Weems, C. Mandolfo, and T. Sandoval.